Association between playing tactics and creating scoring opportunities in elite football. A case study in Spanish Football National Team - Gonzalez-Rodenas, J.; Lopez-Bondia, I.; Calabuig, F.; James, N.; Aranda, R. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to examine the association between playing tactics, situational variables and creating scoring opportunities according to the type of start-up possession in a case-study. All team possessions (n=857) developed by the Spanish Football national team during the World Cup 2010 were analysed and grouped into "strategic set-plays" (n=90), "recoveries" (n=451) and "restarts" (n=316). Fourteen categorical variables which describe offensive playing tactics, opponent situation as well as situational variables and their associations with creating scoring opportunities were examined using chi-square analysis and bivariate logistic regressions. Chi-square analysis showed that "strategic set-plays" were more effective to produce scoring opportunities (29.2%) than recoveries (15.4%) and restarts (8.9%) (P<0.001). Within the strategic set-plays, no differences were found between corners kicks and free kicks to produce scoring opportunities. In recoveries, the variables "field starting zone" (P=0.001), "initial penetration" (P<0.001), "initial opponent number" (P=0.004), "initial opponent position" (P=0.014), "initial penetration zone" (P<0.001), and "type of progression" (P=0.049), and for restarts "pass number" (P=0.049) and "duration" (P=0.006) were associated with the likelihood of creating scoring opportunities. More scoring opportunities were created in the second half (P=0.022). The type of start-up possession and the match half may modify the playing tactics developed during the offensive process and influence the creation of scoring opportunities in Football